DETERMINASI KOMPENSASI, LINGKUNGAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL DINAS PENDAPATAN DAERAH PROVINSI KEPULAUAN RIAU - Anggraeni, Nina; Ngaliman, Ngaliman (Zona Manajerial: Program Studi Manajemen (S1), 2019)
This study describes the purpose Determination of Compensation, Work Environtment and Organizational Commitment Of Performance Employee On Province Riau Islands Department of Revenue Services. The research method used survey method, in which the respondent as many as 80 people as population and drawn sample of 91 people with a sample proportional random sampling method using Slovin formula with looseness rate of 5%. Collection of data techniques using the instrument from the questionnaire form for variable analsisis. These results indicate that compensation determination significant on performance employee, work environment determination significant on performance employee and organizational commitment variables determination significant on performance employee. While simultaneously discovered that there is significant influence between three variables of compensation, work environment and organizational commitment of performance employeeÂ